Comparative Analysis of the Microbial Community Structures Between Healthy and Anthracnose-Infected Strawberry Rhizosphere Soils Using Illumina Sequencing Technology in Yunnan Province, Southwest of China - Su, Daifa; Chen, Shanyan; Zhou, Wenxing; Yang, Junyu; Luo, Zhiwei; Zhang, Zhenrong; Tian, Yunxia; Dong, Qionge; Shen, Xuemei; Wei, Shijie; Tong, Jiangyun; Cui, Xiaolong (Frontiers in Microbiology, 2022)
Strawberry anthracnose caused by Colletotrichum spp. was widespread in recent years, and resulted in great damage to strawberry production. Rhizosphere soil microbial community compositions and structures between healthy and anthracnose infected strawberry were remained unclear. In the present study, a high throughput sequencing technique was used to comparatively study the prokaryotic and fungal community compositions and structures of healthy and anthracnose infected strawberry rhizosphere soils in Yuxi, Yunnan Province. Both microbial community diversities and richness of anthracnose infected strawberry rhizosphere soils were higher than those of healthy strawberry rhizosphere soils. A total of 2518 prokaryotic and 556 fungal OTUs were obtained at the 97% similarity threshold. Proteobacteria, Thaumarchaeota and Acidobacteria were the dominant prokaryotic phyla; Ascomycota, unclassified_k__Fungi and Mortierellomycota were the dominant fungal phyla. The relative abundances of beneficial phyla Actinobacteria and Firmicutes, beneficial genera Streptomyces, Azospirillum and Bacillus were significantly reduced in anthracnose infected strawberry rhizosphere soils. Besides Colletotrichum, 15 other potential fungal pathogen genera and 7 fungal pathogens species were identified; among the potential pathogen genera and species, 8 pathogen genera and Fusarium oxysporum showed significant differences between healthy and anthracnose infected strawberry rhizosphere soils. The results suggested that strawberry planted in this area may be infected by other fungal pathogens except for Colletotrichum spp. This study is the first time to compare the differences of both prokaryotic and fungal communities between healthy and anthracnose infected strawberry rhizosphere soils in an open field.